Political and Legal Analysis of the Delay in Ratifying the Asset Forfeiture Bill: The Role of President Jokowi and the Indonesian House of Representatives - Sambora, Riky; Prasetyoningsih, Nanik; Satriawan, Iwan; Marlinda, Ajeng Puspa; Tamara, Amelia Puspa (Journal of Islamic World and Politics, 2025)
This study examined the delay in the passage of the Asset Forfeiture Bill in Indonesia, despite President Joko Widodo's (Jokowi) strong support. This study identifies several key factors influencing the legislative process, including internal political resistance in parliament, government priorities for economic development, and inconsistent policies. This study used qualitative approaches and thematic analysis to examine the legislative process's complex political, economic, and institutional contexts. The findings showed that the dynamics of political coalitions, the government's focus on infrastructure and foreign investment, governance challenges in ratifying the draft law included in the Prolegnas, and the COVID-19 pandemic are the main inhibiting factors. The study also emphasized the need to align national policies and laws with international legal standards, such as the 2003 United Nations Convention Against Corruption (UNCAC), to accelerate legal reform in the fight against corruption in Indonesia. This research provides important insights for policymakers and the public regarding legislative efforts during President Joko Widodo's administration to eradicate corruption through the legal framework of asset confiscation.